Nail changes in immuno-bullous disorders: A cross-sectional study - Priya P Kadu; Mahendra M Kura (Wolters Kluwer Medknow Publications, 2023)
Context: Autoimmune blistering (AIBD) disorders affect mucosae, skin, and appendages. Appendageal involvement has not been studied extensively to date. However, they are important as nail changes are commonly encountered during a flare-up of the disease. Aims: To determine the prevalence and patterns of nail changes in various Immunobullous disorders and to study the relationship between the nail changes and the disease duration and severity. Settings and Design: A cross-sectional study was conducted at the Department of Dermatology, venerology, and leprosy at a tertiary care center in Mumbai. Materials and Methods: A cross-sectional study including a total of 74 cases of Immunobullous diseases was conducted and the prevalence of nail changes was determined. The association between the mean number of nail changes and the disease duration and severity was analyzed using ANOVA (Analysis of variance) and unpaired t-test. Statistical Analysis: The Statistical Package for Social Studies (SPSS) software was used for statistical evaluation. Results: We found that the prevalence of nail changes was 91%. There was a significant difference in the mean number of nail changes with respect to the severity grades of mucosal involvement in AIBD (P value < 0.05). There was no significant difference in the mean number of nail changes with respect to the severity grades of Pemphigus vulgaris (PV), Pemphigus foliaceous (PF), subepidermal blistering diseases, and the duration of AIBD. Conclusions: Nails are frequently affected in AIBD. The number of nail changes is related to the severity of mucosal disease but not to duration.